Evaluasi Penyimpanan Obat di Apotek Kita Kota Jambi - Pratama, Septa (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2022)
Background: How medications are stored affects both how well they work as treatments and how safe they are from theft. It should be important to store medications in a way that prevents hazards. The existence of an unsuitable and orderly arrangement of drugs as well as a confined spatial arrangement makes the drugs situated inappropriately based on their place and distribution. The negative impact generated by damaged pharmaceuticals is not just for patients, but also has a consequence on the pharmacy itself. Objective: This study aims to evaluate the drug storage system at Apotek Kita based on the technical guidelines for pharmaceutical standards at the Pharmacy in 2019. Methods: This research is a descriptive observational study, which intends to look at the medication storage system at Apotek Kita. Results: Based on the results of the research conducted, it can be determined that drug storage at Apotek Kita is entirely in accordance with the Technical Guidelines for Pharmaceutical Service Standards at Pharmacies in 2019, as can be seen from the appropriate percentage of 95.65%. Conclusion: The percentage of storage that is suitable for completing appropriate medication storage criteria shows that Apotek Kita has implemented a good medication storage system.